2022
DOI: 10.3390/infrastructures7020018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Driver’s Socioeconomic Characteristics Relating to Speeding Behavior and Crash Involvement: A Case Study in Lahore

Abstract: Speeding is one of the risky behaviors which results in accident involvement causing fatalities and severe injuries. This paper aimed to identify the significant socio-economic characteristics of drivers concerning their speeding behavior and crash involvement. A questionnaire was designed consisting of driver’s demographic features, involvement in an accident, penalty on speed violations, and statements on speeding behavior in terms of exceeding the speed limits by 10 km/h or more on roads with different spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
6
1
Order By: Relevance
“…Contrary to most findings, a study in Lahore, Pakistan, using the TPB, found that certain attitudes had a negative association with speeding intentions, while subjective norms and traffic enforcement awareness were positively correlated [36].…”
Section: An Overview Of the Prevalence Of Speeding And Factors Affect...contrasting
confidence: 65%
“…Contrary to most findings, a study in Lahore, Pakistan, using the TPB, found that certain attitudes had a negative association with speeding intentions, while subjective norms and traffic enforcement awareness were positively correlated [36].…”
Section: An Overview Of the Prevalence Of Speeding And Factors Affect...contrasting
confidence: 65%
“…We can attribute this finding to higher noncompliance with the rules of the road. Previous studies have shown that higher noncompliance with road-design requirements is associated with more severe crashes [17,[35][36][37].…”
Section: Results Of the Crash-severity Modelmentioning
confidence: 98%
“…Previous studies have indicated that there is a relationship between drivers' socioeconomic demographics (SEDs) and their likelihood of being involved in speeding behavior and traffic crashes [17]. Different age-groups are associated with distinct psychological and physiological features that affect how they react to unexpected situations (e.g., a traffic accident) [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the course of studying the types, causes, factors and conditions contributing to the occurrence of traffic accidents, it was found that most deaths occur as a result of collisions and collisions with pedestrians. In scientific papers [11], one of the main factors affecting the severity of the consequences of the traffic accident is considered -exceeding the speed limit. Drivers often exceed the speed limit to reduce time, not perceiving and underestimating the possible consequences.…”
Section: Analysis Of the Main Types Accidents With A High Mortality Ratementioning
confidence: 99%